2019
DOI: 10.14309/ajg.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Real-World Effectiveness of Competing Colonoscopy Preparations: Results of a Prospective Trial

Abstract: OBJECTIVES: Despite the importance of adequate bowel cleansing prior to colonoscopy, national societies provide little guidance regarding which bowel preps are best tolerated and most effective; this reflects a lack of comparative effectiveness studies that directly evaluate available preps in a "real-world" setting. To address this gap, we conducted a prospective, naturalistic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
2
25
0
1
Order By: Relevance
“…128 In recent years, a new bowel preparation agent containing magnesium sulfate, which can be used in both the 1-day preparation and split dosing method, has been used in the US. Even in non-RCTs, it showed that it was as effective as other bowel preparation agents, 129 with clinical trials currently ongoing in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…128 In recent years, a new bowel preparation agent containing magnesium sulfate, which can be used in both the 1-day preparation and split dosing method, has been used in the US. Even in non-RCTs, it showed that it was as effective as other bowel preparation agents, 129 with clinical trials currently ongoing in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al found in a large non-commercial ‘real-world’ prospective multicenter trial with 4339 colonoscopies and 75 endoscopists that MiraLAX with Gatorade, MoviPrep and Suprep were associated with superior tolerability and bowel cleansing. 8 As tolerability of bowel preps should be optimised for clinical trial participants with active IBD, bowel preps should be selected accordingly. Polyethylene glycol 3350 and some form of an electrolyte balanced sports drink may be ubiquitously available, and this combination may also be optimal because PEG based bowel prep regimens seem to have the lowest rate of bowel prep induced mucosal artefacts.…”
Section: Acquisition Stagementioning
confidence: 99%
“…Gu et al provided a prospective, naturalistic comparative effectiveness study to assess the effectiveness and tolerability of different colonoscopy preparations. 10 This makes it more applicable to the outpatient setting, as patient tolerability can determine preparation effectiveness and was Mrs. Smith's primary concern. The level of evidence of this study is 2 using the SORT algorithm, as it is an observational study.…”
Section: Related Literaturementioning
confidence: 99%
“…Patients were also not excluded for having chronic conditions such as chronic opioid use, inflammatory bowel disease, chronic kidney disease, congestive heart failure, and cirrhosis. 10 This is in contrast to the RCTs previously listed, which typically include fewer, more controlled regimens and excluded patients with chronic conditions. 1,4,5 This study was also free of the Hawthorne effect and remuneration, as it was not a RCT.…”
Section: Critical Appraisalmentioning
confidence: 99%